Necrotizing fasciitis of the neck: considerations about two cases - Giordano, Davide; Pernice, Carmine; Pedroni, Corrado; Barbieri, Verter (Acta Biomedica Atenei Parmensis, 2014)
Background and Aim: Necrotizing fasciitis is a rapidly progressing life-threatening infection of the deep fat and fascial layers which rarely occurs in the neck. The aim of the paper is to report the management of this rare condition pointing out the role of multimodality in achieving the cure of the patient. Methods: we report our experience regarding management of two cases of necrotising fasciitis of the neck successfully treated with medical and surgical therapy. Discussion: Early diagnosis of necrotizing fasciitis of the neck plays a central role in preventing progression of the disease. Multimodal treatment should be mandatory. Conclusions: Immediate aggressive surgical debridement, securing of the airway, and anti-bacterial agents represent the only effective treatment in preventing progression of the disease. Intensive care support should be considered integral part of treatment.